Marsdenia tenacissima extract dilated small mesenteric arteries via stimulating endothelial nitric oxide synthase and inhibiting calcium influx. (28th June 2019) - Hao, Huifeng; Tian, Wenjia; Pan, Chunshui; Jiao, Yanna; Deng, Xinxin; Fan, Jingyu; Han, Jingyan; Han, Shuyan; Wang, Miao; Li, Pingping
Abstract: Ethnopharmacological relevance: Marsdenia tenacissima is a traditional Chinese medicine that is known to be effective in combating cancer as well as reducing blood pressure. The efficacy and mechanisms of Marsdenia tenacissima in treating cancer have been well described. However, the potential vasoactivities of Marsdenia tenacissima remain poorly known. Aim of the study: To determine the vasoactive effects of the water-soluble part of marsdenia tenacissima in mesenteric resistance arteries of the mice, and to explore the underlying mechanisms. Materials and methods: Isometric vessel tension study was used to examine the effects of marsdenia tenacissima extract (MTE) on vasodilation of the mesenteric arteries of mice. KCl, phenylephrine (PE) and 9, 11-Dideoxy-11α, 9α-epoxymethanoprostaglandin F2α (U46619) were used as vasoconstrictors. Y27632, Nitro-L-arginine methyl ester hydrochloride (L-NAME) and indomethacin were used to explore the underlying mechanisms for the vasoactivities of MTE. Western blot and nitric oxide (NO) assay were used to evaluate the effects of MTE on the activities of endothelial nitric oxide synthase (eNOS). Results: MTE (5–50 mg/mL), but not vehicle, dose-dependently relaxed the mesenteric arteries constricted with KCl, PE or U46619, in which relaxations to KCl were more pronounced than that to PE or U46619. Pre-incubation of the vessels with MTE (40 mg/mL) reduced the vasoconstrictions caused by calcium influx. Decreasing calcium sensitivity by inhibition of Rho kinase (ROCK) significantly augmented the vasorelaxation of MTE. While, inhibition of endothelial cells by pre-incubation with L-NAME (300 μM) and indomethacin (10 μM) or denudating endothelial cells attenuated vasorelaxations of MTE to KCl, and with a larger potency, to U46619. In both human umbilical vein endothelial cells (HUVECs) and human heart microvascular endothelial cells (HMECs), the phosphorylations of eNOS and the production of NO were significantly enhanced after treatment of MTE for 2, 5, 10, 30 min. Conclusions: MTE, the water-soluble part of marsdenia tenacissima, was effective in relaxing mesenteric resistance arteries via inhibiting calcium influx and stimulating eNOS activities. Graphical abstract: Image 1